Unified Model for Calculating Technical Facilities Productivity for Transportation and TransportationTechnological Operations - O. S. Vorotnikova; N. A. Maystrenko; A. G. Levshin (Сельскохозяйственные машины и технологии, 2021)
Productivity is one of the important performance indicators of transport and transport-technological vehicles. The authors confirmed the necessity to unify this indicator calculations for an extensive range of agricultural goods and extensive works on their movement. (Research purpose) To develop universal interconnected stages of detecting the operational productivity of transport and transport-technological vehicles when performing mechanized work in crop production. (Materials and methods) The values of operational performance were determined based on the analysis of norm-forming factors and statistical processing. A systematic approach was used to identifying individual elements of the cargo transportation cycle. The authors studied each of the methodological approaches and the mathematical tools used to calculate the performance indicators of various technical devices. (Results and discussion) After a step-by-step modeling of transport and transport-technological processes, a unified formula of the target function (optimality criterion) was obtained. Having implemented a more convenient calculation algorithm and having transformed the mathematical apparatus, the authors obtained the vehicle production rates for the transportation of mineral fertilizers to the place of their application. (Conclusions) The authors implemented a detailed mathematical description of the transport and transport-technological process stages. They identified the functional relationships between operational parameters and production and agrolandscape conditions.  A universal algorithm was developed making it possible to determine the values of the operational performance for transport and transport-technological vehicles. The authors determined the values of the coefficient enabling the unification and comparison of the algorithm for identifying the production rates for transport and transport-technological work. It was found out that with an increase in the length of transportation from 3 to 54 kilometers, this coefficient increases 3.8 times. This variation was explained by an increase in the purely transport phase of the process.